IMPLEMENTATION OF LOCAL WISDOM-BASED PROCEDURAL TEXT WRITING IN INDONESIAN LANGUAGE SUBJECTS BASED ON THE PHINISI BOATBUILDING PROCESS IN SENIOR HIGH SCHOOLS - Muhammad Asdar; Anshari Anshari; Mayong Maman; Mantasiah R (Adisam Publisher, 2025)
Indonesian language lessons in high school can be enriched by integrating local wisdom, such as the process of making Phinisi boats, into procedural text materials. This aims to foster a sense of cultural love, strengthen local identity, and improve students' procedural writing skills. This implementation can be done through various learning strategies, such as discussion, observation, project, and creative writing. Local wisdom is a valuable cultural heritage and needs to be preserved. One way to preserve local wisdom is by integrating it into school learning. Indonesian language lessons, especially procedure text material, are the right medium to introduce and instil noble values of local wisdom to high school students. local wisdom that can be integrated in procedure text material is the process of making Phinisi boats. The Phinisi boat is an Indonesian maritime cultural heritage that is full of meaning and noble values.expand_more The manufacturing process reflects the local wisdom of the Bugis-Makassar people in utilising natural resources and their expertise in seafaring.